Hydrochemical characterisation and identification of seawater intrusion in the Visakhapatnam coastal aquifer - Venna Mythilee Priyanka; Ramesh Maddamsetty; Srinivas Yarramalle (IWA Publishing, 2023)
Groundwater dependency has increased due to several factors like population increase, industrialization, and climate change impact. Analysis of groundwater is important to know the present status and also for better management of natural resources. Groundwater samples from 41 locations were collected along the study area during the pre and post-monsoon seasons, and samples were analysed for pH, EC, total dissolved solids (TDS), major cations, and anions like Ca2+, Mg2+, Na+, K+, Cl−, HCO3− and SO42−. From the chemical analysis results, seawater intrusion is identified through qualitative approaches, i.e., Simson ratio (Cl/(HCO3 + CO3) and Na/Cl ratio. Simson ratio ranges between 0.316 to 2.119 during pre-monsoon and 0.124 to 3.947 during post-monsoon, and from Na/Cl ratio, 30 samples fell under seawater intrusion during pre-monsoon and 38 samples during post-monsoon. The Simpson ratio results also show that seawater intrusion is reducing during the post-monsoon due to increasing groundwater levels caused by rains. From the water quality index classification, 4.88% of the water samples fell under excellent in both seasons, and the rest of the samples were all in the remaining four classes. The spatial analysis was also done to understand the changes in groundwater quality and seawater intrusion over space. HIGHLIGHTS Assessment and status of groundwater quality in the coastal area.; Factors controlling groundwater quality in the study area.; Analysis of seawater intrusion risk assessment.; Identification of water suitability for drinking purposes.; Spatial analysis for identification of areas under threat.;